Rheological behavior of mechanically stabilized and surfactant-free MWCNT-thermal oil-based nanofluids - Ilyas, S.U. (Elsevier Ltd, 2017)
The viscosity of nanofluids is one of the important parameter for the design of heat transfer processes. The evolution of usage of nanofluids in heat transfer processes is gaining more industrial consideration due to excellent thermal properties. However, limited attention is focused on the rheological behavior of nanofluids as of today. The multiwall carbon nanotubes (MWCNTs) are stabilized in thermal oil using ultrasonication and high stability is observed. The rheological behavior of thermal-oil based dispersant-free nanofluids are studied at varying high shear rates (100–2000 s− 1), temperatures (25–90 °C) and nanoparticle concentrations (0.1–1 wt). The effect on the shear stress and viscosity by the addition of carbon nanotubes in thermal oil is discussed. The measured effective viscosity is compared with different theoretical conventional models. A significant increment in relative viscosity is observed at high concentrations of carbon nanotubes. A correlation is developed based on the temperature, nanomaterial concentration, and shear rate. © 2017 Elsevier Ltd